NUMERIC INTEGRATION, ALGORITHMS - Raffo Lecca|, Eduardo (2007)
In this article are developed and implemented, the integration of numerical algorithms, which allow solve problems in science and engineering, such as the calculation of areas, volumes, applied mechanics, differential equations (dynamic systems). Given the need for a high-precision, he examines the different rules of numerical integration; based on the errors that occur when the integrand is replaced by a polynomial interpolation P (x), known as the formulas of integration Newton - Cotes. The rule of Richardson extrapolation can be applied to any formula squaring Newton- Cotes, or any computer which is based on a grid of wide h and error described as a power h.